CHI '08 Extended Abstracts on Human Factors in Computing Systems 2008
DOI: 10.1145/1358628.1358891
|View full text |Cite
|
Sign up to set email alerts
|

User experience over time

Abstract: The way we experience and evaluate interactive products develops over time. An exploratory study aimed at understanding how users form evaluative judgments during the first experiences with a product as well as after four weeks of use. Goodness, an evaluative judgment related to the overall satisfaction with the product, was largely formed on the basis of pragmatic aspects (i.e. utility and usability) during the first experiences; after four weeks of use identification (i.e. what the products expresses about i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 11 publications
0
42
1
Order By: Relevance
“…This is also related to the individual's limited processing capacity, which leads to applying selective attention as a way to extract the most important information for processing (Strayer and Drews, 2007). When it comes to processing personal data, the user is also likely to identify with the information and personalise the related viewing behaviour, such as only looking at information that he or she deems valuable (Karapanos, 2013). Some users are more likely to selectively attend to positive feedback because it seems more believable (Hixon and Swann, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…This is also related to the individual's limited processing capacity, which leads to applying selective attention as a way to extract the most important information for processing (Strayer and Drews, 2007). When it comes to processing personal data, the user is also likely to identify with the information and personalise the related viewing behaviour, such as only looking at information that he or she deems valuable (Karapanos, 2013). Some users are more likely to selectively attend to positive feedback because it seems more believable (Hixon and Swann, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study (N = 10) showed that during the first week of operating an interactive TV set-top box, aspects of the product such as perceived utility and ease of use mainly influenced the overall evaluation of the product, whereas after four weeks, the users' identification with the product became the primary predictor of its perceived usability (Karapanos et al, 2008). Another study (N = 8), examined change in user-product relationship among expert users of mobile phones, using a post-usage interview technique (von WilamowitzMoellendorff et al, 2006).…”
Section: A Longitudinal Approach To Usability Testingmentioning
confidence: 99%
“…Would they identify value, or would their interactions disrupt the interpretations recurrent users found? Whilst research has argued the need to improve understanding of technological appropriation in public spaces, where users and practices are heterogeneous and dynamic [1,12,22,32], there is a lack of practical guidance on how to support this though embedded media. Although research has considered how users interact in different ways with wall displays (i.e.…”
Section: Supporting and Studying Public Appropriationmentioning
confidence: 99%